In Diplomatic Banquet of Treaty: Islamic Sharī‘ah and International Laws Share the Attires of Pacta Sunt Servanda (American Journal of Islam and Society, 2012)
The importance of treaties in international relations cannot be overemphasized especially now that the contemporary world has radically changed to a global village’. It has been observed as far back as 1960s that “modern international law can hold the allegiance of the world at large only by establishing its claim to continuing acceptance as a synthesis of the legal thought of widely varying tradition and culture.”1including Islamic law. Hugo Grotius drew most of his ideas of modern international law from the Bible and from the St. Augustine’s just war theory. It is not surprising, therefore, that treaties under modern international law are based on good faith. “The ideal of law in Islam is based on good faith. . . .”2 This is an indication that Islamic law and modern international law must have come from the same source. Treaties, therefore provide a veritable opportunity to attempt a harmony and a communality between the two legal regimes with a view to achieve, despite the complexity and diversity of human society, a common universal understanding that ensures peace and cooperation across the globe. This article aims at achieving that objective